KAJIAN KETERKAITAN ANTARA KARAKTERISTIK DAN PERMINTAAN USAHA MIKRO DAN KECIL YANG BERBAHAN BAKU BERAS DI KECAMATAN BUAHBATU KOTA BANDUNG - Putri, Safira Aulia; Saidah, Zumi (Universitas Galuh, 2023)
The pattern of demand and the characteristics of rice-based SMEs are closely related. This is because the pattern of demand for SME rice is a pattern that describes the need for SME rice and can influence the decisions of SME entrepreneurs in managing their business. This study aims to examine the relationship between the characteristics and demand patterns for SME rice in Buahbatu District, Bandung City. The data collected includes primary and secondary data. The sampling technique used in this study is a combination of Stratified Random. The sample used in this study was 59 respondents. Data analysis technique is done by descriptive analysis. The results of the study show that in general the majority of UKM owners are men with junior high school education, aged around 41-50 years with a family of 3 dependents, have been in business for ≤ 5 years, and are micro-enterprises. Most SMEs buy rice with a frequency of 30 times/month with a total of 235 kg/month and an average sale of 87 portions/day. The price of purchased rice is IDR 12,500/kg with a total expenditure of IDR 3,221,949/kg.